Prarancangan Pabrik Biodiesel dari Minyak Jarak Pagar dan Metanol Kapasitas 30.000 Ton/Tahun - Purnomo, Joko, Dr. Achmad M. Fuadi, M.T, Ir. Nur Hidayati, M.T., Ph.D (2015)
Requirement of fuel oil (BBM) in Indonesia is increasing from year to year. The rate of fuel consumption is followed by a further decline in oil production in the country. In 2005 a fact stated that Indonesia has become a net oil importer. The increase in world crude oil prices have a large impact on the national economy. The solution to overcome the dependence on fossil fuels is to set up a biodiesel plant of castor oil and methanol with a capacity of 30,000 tons per year is planned to be in operation for 330 days per year. The process of making biodiesel from castor oil and methanol, carried through in the transesterification process flow stirred tank reactor (RATB). In the reactor the reaction at liquid-liquid phase at a temperature of 60ºC feed, pressure 1 atm and resulted in a conversion of 98%. Of these conditions the plant is classified as low-risk plant operating conditions at atmospheric pressure. The process of formation of Jatropha oil into methyl ester , first castor oil reacted with meanol and will produce diglycerid and methyl ester , then the results of diglycerid react with the alcohol molecules other and will produce monoglycerides and methyl esters and results of monoglycerides react with alcohol the third will produce glycerol and methyl esters . Castor oil needs at this plant as much as 3787.88 kg per hour and for the needs of methanol as much as 1575.71 kg per hour . And products in the form of methyl esters as much as 7290.86 kg per day This factory will be established area Boyolali and use of Rp.162.377.089.498,81 fixed capital and working capital of Rp.150.297.112.764,45 . The factory of the economic analysis indicates a pre-tax profit Rp.138.219.456.945,20 per year after taxes 30 % profit reached Rp.96.753.619.861,64 per year . Percent Return On Investment ( ROI ) before tax after tax 42.56 % and 29.79 % . Pay Out Time ( POT ) before tax for 2.1 years and 2.9 years after tax . Break Even Point ( BEP ) of 56.95 % , Shut Down Point ( SDP ) amounted to 30.79 % , Discounted Cash Flow ( DCF ) accounted for 32.25 % . From the results in get concluded , that the plant is profitable and feasible to set .